Deglaciation sequences in the Permo-Carboniferous Itarare Group, Parana Basin, southern Brazil - Vesely, Fernando Farias; Assine, Mario Luis (Elsevier B.V., 2006)
The Late Carboniferous-Early Permian Itarare Group is a thick glacial unit of the Parana Basin. Five unconformity-bounded sequences have been defined in the eastern outcrop belt and recognized in well logs along 400 km across the central portion of the basin. Deglaciation sequences are present in the whole succession and represent the bulk of the stratigraphic record. The fining-upward vertical facies succession is characteristic of a retrogradational stacking pattern and corresponds to the stratigraphic record of major ice-retreat phases. Laterally discontinuous subglacial tillites and boulder beds occur at the base of the sequences. When these subglacial facies are absent, deglaciation sequences lie directly on the basal disconformities. Commonly present in the lowermost portions of the deglaciation sequences, polymictic conglomerates and cross-bedded sandstones are generated in subaqueous proximal outwash fans in front of retreating glaciers. The overlying assemblage of diamictites, parallel-bedded and rippled sandstones, and Bouma-like facies sequences are interpreted as deposits of distal outwash fan lobes. The tops of the deglaciation sequences are positioned in clay-rich marine horizons that show little (fine-laminated facies with dropstones) or no evidence of glacial influence on the deposition and likely represent periods of maximum ice retreat. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deglaciation sequences; Permo-Carboniferous; Itarare Group; Parana Basin